Fictosexuality, Fictoromance, and Fictophilia: A Qualitative Study of Love and Desire for Fictional Characters - Karhulahti, Veli-Matti; Välisalo, Tanja (Frontiers in Psychology, 2021)
Fictosexuality, fictoromance, and fictophilia are terms that have recently become popular in online environments as indicators of strong and lasting feelings of love, infatuation, or desire for one or more fictional characters. This article explores the phenomenon by qualitative thematic analysis of 71 relevant online discussions. Five central themes emerge from the data: (1) fictophilic paradox, (2) fictophilic stigma, (3) fictophilic behaviors, (4) fictophilic asexuality, and (5) fictophilic supernormal stimuli. The findings are further discussed and ultimately compared to the long-term debates on human sexuality in relation to fictional characters in Japanese media psychology. Contexts for future conversation and research are suggested.